Constructing a small scale hydroelectric generator for home use - Mira Yusleeza Binti Mohd Yusoff (Department of Electronic Engineering Technology, Faculty of Engineering Technology, University Malaysia Perlis, 2014)
Hydroelectric is the energy that produces from the water as the main source. Nowadays, people start to findthe alternative way to reduce the electricity bill by using natural resources as alternative energy such as wind and solar to generate electricity. However, both systems are not suitable for all areas and locations. Therefore, this project is an idea to develop a small scale hydroelectric generator system by using consuming water distributedto houses as an alternative electrical energy source for home use.The water pressure and flow inside the pipe from water tank is used to rotate the hydro turbine to drive the mechanical shaft. Kineticenergyis producedby the movement of turbine.